2022
DOI: 10.1186/s13102-022-00553-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing performance and injury risk in elite female Gaelic team sport players and future research directions: a narrative review

Abstract: Background Sports science research in elite female Gaelic team sports has increased in recent years, but still a large disparity exists between the volume of studies involving male and female players. As a consequence of this, it is difficult for practitioners to develop an evidence-based approach when working with female players. Main body In this review, we discuss the current research available in elite female Gaelic team sports with focus on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…This is in line with the literature on Olympic athletes which discovered female athletes were at higher odds of illness [ 10 ]. Despite females making up nearly 50% of sports participants, they are often neglected in the literature with a mere 4% of research devoted to female-only cohorts [ 36 ]. They are often characterised as “more difficult” to study than men due to their level of hormonal intricacy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with the literature on Olympic athletes which discovered female athletes were at higher odds of illness [ 10 ]. Despite females making up nearly 50% of sports participants, they are often neglected in the literature with a mere 4% of research devoted to female-only cohorts [ 36 ]. They are often characterised as “more difficult” to study than men due to their level of hormonal intricacy [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…While nothing conclusive can be drawn from the present results, our findings support the idea that female GAA athletes may benefit from nutrition education programs [ 46 ]. Previous work has shown that this group have poor nutritional knowledge, not to mention a high prevalence of low energy availability, both of which may negatively impact dietary behaviour [ 36 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Important activity patterns, such as evading opponents, winning possession of the ball, breaking tackles, blocking, and intercepting are required for successful performance within the sport. These key technical activities require players to develop appropriate physical characteristics (e.g., aerobic endurance, speed, agility, and muscular strength) that will allow for the successful execution of skills and tolerate the demands imposed by the game (17).…”
Section: Introductionmentioning
confidence: 99%
“…Injury management strategies may include manual therapy, rehabilitation exercises, and graduated return to play (RTP). Both can improve athlete availability and enhance key performance indicators (KPIs) in female athletes ( 15 , 16 ). These duties should ideally involve cross-disciplinary collaboration of suitably qualified strength and conditioning professionals, allied healthcare professionals (AHPs) (e.g., athletic therapists), and traditional medical professionals (e.g., general practitioners) ( 15 , 17 ).…”
Section: Introductionmentioning
confidence: 99%